Bodily Self-Reflection in Sigitas Parulskis’s Naked Clothes - Skikaitė, Izabelė (Semiotika, 2025)
Examining corporeality in Parulskis’s Naked Clothes, we address a problem related to paradigmatic literary corpus analysis: can we reveal the coherence of the text composed of various essays by paying attention to a single thematic isotopy? Analyzing body figures, we combine semiotics and psychoanalysis to explain the connection between the enunciator’s body parts and his affections. Body parts – such as the female cavity and the male “growth” – gain their meaning in relation to individual and collective actors. The analysis revealed that the text, consisting of individual essays, has an integral semantic universe. The text’s coherence is ensured by isotopies such as body parts, movement, sexuality, and their interconnection is elucidated by the psychoanalytic concept of symbolic castration. This concept expounds the semantic connection between several types of anxieties in Parulskis’s texts: the fear of losing one’s body parts, the anxiety of sexual relationships, and the fear of travelling. Analysis demonstrates that corporeality is articulated not by the soul / body dichotomy, emphasized by Parulskis’s literary critics, but by the semantic category of fragmentation / integrity. This category is linked to the unsolvable dilemma: whether the integrity of one’s own body can be ensured by being alone or only together with a woman when creating an androgynous whole.